A busca do Prêmio Nacional da Qualidade por uma empresa do pólo petroquímico do estado de São Paulo: um estudo de caso - Cano, Carlos Roberto (2006)
This work aims to investigate and describe phases and procedures performing by a Paulista Company in order to compete for the Prêmio Nacional de Qualidade PNQ (National Quality Award), during 2003 and 2004 by using PNQ excellence criteria. For this, there was an investigation and a description from quality concepts of the 20th Century most expressive authors, the main quality awards historical, the FNPQ fundamentals and criteria, in order to obtain the National Quality Award, besides the quality historic from the company and its difficulties during the implementation process for pursuit the owners excellence. It was used qualitative research methodology studying a single case, with 17 semi-arranged interviews with directors and managers, in addition to documental analysis on the company, and bibliographic research. At the end, the conclusion was that: in eight PNQ excellence criteria in 2004, five had lower results comparing to 2003, one was kept and only two lowly contributed to excellence improvements, i.e., the improvement points considered relevant to the performance evaluation.